2016
DOI: 10.1037/xge0000169
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of habitual approach: Failure to suppress irrelevant responses evoked by previously reward-associated stimuli.

Abstract: Reward learning has a powerful influence on the attention system, causing previously reward-associated stimuli to automatically capture attention. Difficulty ignoring stimuli associated with drug reward has been linked to addiction relapse, and the attention system of drug-dependent patients seems especially influenced by reward history. This and other evidence suggests that value-driven attention has consequences for behavior and decision-making, facilitating a bias to approach and consume the previously rewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
29
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
7
29
4
Order By: Relevance
“…Results of the flanker task are in line with data recently obtained by our group (Leganes-Fonteneau et al 2018) and by others (i.e., Bourgeois et al 2016) demonstrating the ability of reward CS to grab preferential attention implicitly. This interference is also congruent with previous examples of reward conditioning effects on a flanker task (Anderson et al 2012(Anderson et al , 2016a. HR CS, paired with increased probabilities of reward, generated more cognitive Figure 2.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results of the flanker task are in line with data recently obtained by our group (Leganes-Fonteneau et al 2018) and by others (i.e., Bourgeois et al 2016) demonstrating the ability of reward CS to grab preferential attention implicitly. This interference is also congruent with previous examples of reward conditioning effects on a flanker task (Anderson et al 2012(Anderson et al , 2016a. HR CS, paired with increased probabilities of reward, generated more cognitive Figure 2.…”
Section: Discussionsupporting
confidence: 88%
“…However, in this case, as in others (i.e., Anderson 2015), the implicit nature of the effect generated by CS can only be postulated as no stringent measures of CA were implemented. Anderson et al (2012Anderson et al ( , 2016a also reported the effect of CS as distractors on a modified flanker task, but again without examining the implicit aspects of learning.…”
mentioning
confidence: 99%
“…In contrast to the results of Sha and Jiang (2016), but consistent with a large number of prior reports (e.g., Anderson, in press c, 2016a; Anderson et al, 2011a, 2012a, 2013a, 2013b, 2014b, 2016b; Miranda & Palmer, 2014; Roper et al, 2014), reward did not significantly modulate performance in the training phase. However, and most critically, performance was significantly affected by the distractors in the test phase.…”
Section: Discussionsupporting
confidence: 87%
“…Because the distractors are entirely task-irrelevant, they can be implemented in basically any task, including tasks that examine response biases (Anderson et al, 2012, 2016a; see also Krebs, Boehler, Egner, & Woldorff, 2011; Krebs, Boehler, & Woldorff, 2010; Anderson, in press b, for a review). This allows for a broader assessment of the impact of value-driven attention on information processing, and also allows for assessment of generalizability across contexts and situations (Anderson et al, 2012; Anderson, 2015a, 2015b) as well as the enduring nature of the learning (which is only possible under conditions of extinction; Anderson & Yantis, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more directly related to addictions, previously reward-associated but currently task-irrelevant stimuli more strongly evoke an associated response in both a flankers task (Anderson et al, 2012) and a Stroop task (Krebs et al, 2010, 2011). Such stimuli have also been shown to escape inhibitory processing in a cued go/no-go task, with their associated response signals more strongly influencing behavior (Anderson et al, 2016a); that is, response inhibition processes that are normally effective at suppressing the associated behavior signaled by a no-go stimulus fail to do so when that stimulus is previously associated with reward. In summary, when an arbitrary reward-associated stimulus captures attention, this attentional orienting is associated with a bias in approach behavior.…”
Section: Parallels With Normal Cognitionmentioning
confidence: 99%